Factorization of big integer and the security of RSA - Yan-bing REN (网络与信息安全学报)
Three kinds of methods for integer factorization were proposed and the security of RSA was demarcated.RSA is a well-known cryptographic algorithm,using the analysis result of those methods.Through the work,readers could easily realize that if merely enlarged two prime numbers but lost attention of the relevance of them,the security of this algorithm might been missed.In the end,two recommended tactics to choose prime numbers as key of this algorithm were given.